Users’ knowledge and perceptions concerning the Brazilian legislation on electronic nicotine delivery systems: A qualitative study - Neilane Bertoni; Andre Salem Szklo; Tiago Coutinho; Antonio Tadeu Cheriff dos Santos; Fernando Lopes Tavares de Lima (Saúde e Sociedade)
Abstract Since 2009, the commercialization and advertising of electronic nicotine delivery systems (ENDS) have been prohibited in Brazil. RDC-ANVISA N° 855/2024 was published recently, maintaining the bans based on current robust scientific evidence. This study aimed to understand users’ knowledge and perceptions about the Brazilian legislation on ENDS and how it impacts their use behaviors. This exploratory qualitative research was conducted with in-depth interviews using content analysis of three thematic axes: “commercialization”, “Advertising/publicity”, and “environments of use”. Participants were aware of the sales ban, reporting legislation had hindered purchases in physical outlets, but cited the Internet as the primary space for accessing ENDS. They showed that they knew of the ban on advertising/publicity but pointed to digital influencers as central agents in constructing their perceptions about ENDS. They were familiar with the ban on smoking in collective environments. However, they reported that using ENDS is possible because it does not cause a “social nuisance” since they lack unpleasant smoke/smell. Thus, we show that, although the legislation creates obstacles to access/use of ENDS, in practice, such rules are “disregarded/circumvented”. In conclusion, ENDS’ “social acceptability” can renormalize smoking, and it is crucial to run information campaigns about their risks/harms and more effective surveillance.